Kisah Al-Qur’an: Hakekat, Makna, dan Nilai-nilai Pendidikannya - Abdul Mustaqim (Universitas Islam Negeri Mataram, 2011)
Qur’anic stories are among God’s methods to educate human being. They contain moral of stories which send messages to people without indoctrinating. Conversely, they provide some interesting and enjoyable teachings and values. The main objective of the narrative stories of the Qur’an is to give lesson to human beings, along with their two functions, ‘abd al-Lâh (servant of God) who must serve the Lord and as khalîfah al-Lâh (representative of the Lord). By using descriptive analytical method and thematic interpretation approach, the article describes various educational values in the stories of the Qur’an. From some samples of stories in the Qur’an, the writer concludes that there are many educational values in the stories of the Qur’an, namely tauhid (the unity of God), intellectual, moral, sexual, spiritual and democracy values.